Triagem auditiva neonatal universal em uma abordagem ambulatorial: revisão integrativa - Lima, Tatiana Pinheiro (2015)
Neonatal hearing screening (NHS) aims to identify, as early as possible, the hearing loss in newborns and infants. Two main approaches can be adopted in achieving NHS: in the hospital before discharge, and soon after birth, and when this is not possible, in an outpatient setting, after hospital discharge. Outpatient NHS is adopted mainly in countries where the number of births in hospitals is small, in rural areas, or when there is not a sufficient organization to perform NHS in hospitals. In a country like Brazil, it is important to be able to study the possibility of holding the NHS in an outpatient setting, it s efficiency and effectiveness, and quality indicators in our reality full of economic, health, educational and cultural diversities.Objective: To study the results described in the literature on neonatal hearing screening (NHS) in context outpatient through an integrative review.Method: Integrative review.Search Strategy: Databases: MEDLINE, SciELO, lilac'S and SCOPUS. Selection and inclusion of studies: articles describing the NHS in neonates and infants up to three months of age; which included the site of the NHS; who specified age the day of NHS; who described the tests used and its stages; articles in Portuguese, English and Spanish.Results: It was identified 487 references that met the inclusion criteria. After removal of duplicate studies (83) leaving 404 references, analyzed through the titles and abstracts. Of this total, 292 were excluded because they are research with another theme. Thus, 112 references were selected for reading in reading. Of this total, 70 references were excluded. Of these 42 references were selected for addressing the issue, but 27 references were excluded for not answered any of the guiding questions and address a specific theme. Thus references 15 met all inclusion criteria. Of the 15 selected references 10 refer only to the results of the a outpatient Newborn Hearing Screening five reading to screening systematically held between the neonatal hearing screening in the hospital and outpatient model. The Primary care clinic was the most used room for outpatient approach followed by Health Unit Centers. All studies used the OAE for the test and retest. Conclusion: Few studies describing the outpatient NHS, with reliable and appropriate methodology; The NHS is feasible to perform, especially in primary care, but depends on the organization of the local health system. The age of The outpatient NHS vary between the fourth and 56 day of life of the infant and the prevalence of hearing loss observed in outpatient NHS range from 1.5 to 5.96 / 1000